Technology for the Manufacture of Microwave Absorbers from the Dispersed Composite Based on Powdered Activated Charcoal and Iron (III) Oxide - Boiprav, O.V.; Hasanov, M.H.; Bogush, V.A. (Herald of Azerbaijan Engineering Academy, 2024)
The article presents new technology for the manufacture of microwave absorbers. This technology is based on the implementation of the following processes: 1) obtaining a dispersed composite by incorporating finely dispersed iron (III) oxide from a mixture of the latter with a surfactant into particles of powdered activated charcoal; 2) fixing in the matrix of the resulting dispersed composite. The results of the experimental substantiation of this technology are presented. In the frequency range of 2.0–7.0 GHz, the absorption band width of absorbers manufactured in accordance with the presented technology is 3.0 times greater than the effective absorption band width of absorbers made from powdered activated charcoal. These absorbers seem to be promising for use in instrumentation, in particular, in order to protect the elements used for the manufacture of radio measuring instruments, as well as these instruments themselves, from the effects of active and passive electromagnetic interference in the microwave range.